1985
DOI: 10.1002/oms.1210200605
|View full text |Cite
|
Sign up to set email alerts
|

Multiple ionization, charge separation and charge stripping reactions involving polycyclic aromatic compounds

Abstract: The 70eV electron ionization mass spectra of polycyclic aromatic compounds are characterized by the presence of relatively stable multiply charged molecular iolls m]"+ (n=24). When generated from the compounds benzene, napthalene, anthracene, phenanthrene, 2,3-benzanthracene, 1,2-benzanthracene, chrysene, 9,lO-benzopbenanthrene and pyrene, the relative abundances of the multiply charged ions increase dramatically with the number of Mgs. These compounds form multiply charged molecular ions

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
49
1

Year Published

1989
1989
2016
2016

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 67 publications
(55 citation statements)
references
References 22 publications
5
49
1
Order By: Relevance
“…The present experiments show that C 16 expected for C 24 H 5+ 12 a small feature is present. The presently observed critical PAH charge state and multiply charged cations relative intensities are higher than those previously observed for coronene and pyrene using other ionization methods [18,28,43]. Recently, Yatsuhashi and Nakashima observed a high relative yield of multiply charged PAHs (up to 4+) using intense femtosecond-laser pulses [44], but these studies did not include pyrene or coronene.…”
Section: B Multiply Charged Molecular Cationsmentioning
confidence: 64%
See 1 more Smart Citation
“…The present experiments show that C 16 expected for C 24 H 5+ 12 a small feature is present. The presently observed critical PAH charge state and multiply charged cations relative intensities are higher than those previously observed for coronene and pyrene using other ionization methods [18,28,43]. Recently, Yatsuhashi and Nakashima observed a high relative yield of multiply charged PAHs (up to 4+) using intense femtosecond-laser pulses [44], but these studies did not include pyrene or coronene.…”
Section: B Multiply Charged Molecular Cationsmentioning
confidence: 64%
“…For example, in photodissociation and low-energy CID studies of pyrene, the emission of acetylene molecules C 2 H 2 was reported [9,25]. Furthermore, for different small PAHs (up to four fused rings), Kingston et al [43] observed that a charge separation occurs for doubly and triply charged cations, leading to the formation of CH + 3 , C 2 H + 2 , and C 3 H + 3 ions and other charged products. In the case of pyrene an additional decay pathway results in the loss of C 4 H + 2 .…”
Section: Loss Of Neutral and Charged C N H X Moleculesmentioning
confidence: 99%
“…This is in agreement with the earlier work of Kingston et al who observed about a factor of 4 ϫ10 Ϫ8 less triply charged benzene than the singly charged species. 18 The hydrocarbon fragment ions of benzene containing 4 or 5 carbon atoms were mass selected and crossed with the electron beam. The ion signal of these mass peaks is free of contributions of multiply charged molecular ions.…”
Section: Methodsmentioning
confidence: 99%
“…Benzene and other cyclic molecules turn out to resist Coulomb explosion much better than many other small molecules. 9,18,19 Burdick and co-workers observed triply charged molecules of the smallest heterocyclic aromatic compounds C 4 H 4 X ͑XϭNH, O, and S͒. 19 Kingston et al investigated the multiple ionization of polycyclic aromatic compounds.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation